Effectiveness of analgesia techniques for intrauterine device insertion: A systematic review of randomized clinical trials (Research, Society and Development, 2025)
Intrauterine Device (IUD) insertion is a widely used contraceptive procedure but often associated with significant pain, especially among nulliparous women. The lack of clinical consensus regarding the most effective analgesia technique has led to multiple randomized trials evaluating both pharmacologic and non-pharmacologic strategies. This systematic review aims to synthesize evidence on the effectiveness of analgesia techniques used during IUD insertion based on randomized clinical trials. A comprehensive search was performed in PubMed using MeSH terms, with no restrictions on language or publication date. Eligible studies included randomized controlled trials assessing analgesia interventions during IUD insertion with pain measured through validated scales. Duplicates, reviews, commentaries, observational studies and inaccessible full texts were excluded. Ninety-four articles were identified, and sixteen were included in the final analysis. The interventions comprised local anesthetics (spray, gel, cream), oral analgesics, cervical ripening agents, inhaled nitrous oxide, and non-pharmacologic strategies such as acupuncture. Findings showed that 10% lidocaine spray, EMLA 5%, misoprostol and dinoprostone consistently reduced pain scores, while lidocaine gel and nitrous oxide showed no significant benefits. Oral analgesics demonstrated mixed results, with naproxen and tramadol performing better than placebo in specific trials. Acupuncture produced promising analgesic effects. In conclusion, topical anesthetics and cervical ripening agents appear to be the most effective strategies, although methodological heterogeneity remains a challenge. Future research should prioritize standardized pain scales, account for nulliparity, and assess safety and cost-effectiveness.